CONFIDENCE TO DIGITAL CURRENCIES OF CENTRAL BANKS: INSTITUTIONAL PARADOX OR AGE MATTERS (World of finance, 2020)
Introduction. Technological innovations potentially can change monetary systems. The paper raises important problem of confidence in central bank digital currency (CBDC). Because the level of such confidence is variable across countries, it is assumed, that in the core of confidence in CBDC are non-fundamental factors.The purpose is to share the institutional analysis of money on digital currencies and empirical testing of the hypothesis, that confidence in CBDC is not determined by theoretically-driven factors, yet specific factors like age structure of the population.Results. Basing on institutional approach on money it is found that problem of trust into digital currencies is differ that problem of trust into the money during they genesis. It is because of competition between different money forms, different level of issue centralization, different barriers of perception of innovations in area of digitalized money. It is pointed, that confidence in CBDC is not in relations with neither inflation experience of the country, nor spread of fintech in the country. Central banks transparency and rule of law as a criteria of current monetary order efficiency are not in line with the confidence in CBDS. In the same time fraction of younger generation is positively and relatively strongly correlated with confidence in CBDS. Basing on that, some theoretical generalizations are done about fragmentation of such phenomena as “common knowledge” and “money is memory”. Such fragmentation is driven by innovation perception barriers. Nevertheless, it is not deny that confidence in CBDS can expand due to network externalities.Conclusions: The hypothesis, that confidence in CBDS age-driven, is confirmed. This brings new understanding into institutional analysis of money. “Common knowledge” as driver of trust in money could be fragmented, that shouldn’t deny importance of network externalities for further expansion of digitalized money